A cross-sectional study of perception among medical students on online learning amid COVID-19 pandemic, at Government Medical College, Agra, India - Singh, Kunver V.; Aqeel, Khan I.; Misra, S. K. (International Journal Of Community Medicine And Public Health, 2020)
Background: Online learning emerged as an alternative method in time of COVID-19 pandemic. Zoom app, google app, LT software platform etc are helping to minimize the gaps in learning as a consequence of the current circumstances in which conventional teaching is being withheld. We conducted a study to find perception among medical undergraduate students of our college regarding effectiveness of online learning. Methods: This descriptive cross-sectional study was conducted among 600 medical undergraduate students of S.N. Medical College, Agra. A semi-structured, self-administered questionnaire was used and a total of 506 students responded. Data obtained was analyzed and inferences were drawn. Results: We observed mixed perceptions having both favorable as well as unfavorable elements with their first and short experience of online learning. Majority of students found time flexibility (58.8%) and location flexibility (62%) in online learning as beneficial. While three-fourth (77.5%) missed interest created in collective learning. Majority also felt lack of concentration (59.7%), understanding (51.0%) and interaction (67.2%) with online learning. Around two-third of them reported technical malfunctioning and also pilling up of lesson material. Half of the student stated that home environment was not conducive for online learning. 71.2% wanted both online learning and conventional learning as future mode of learning after the end of pandemic. 28.3% recommended improvement in the online learning. Conclusions: This study found mixed perceptions regarding online learning. This study also provided valuable inputs which can be utilized to improve effectiveness and quality of online medical education delivery in future.